Outcomes of active surveillance of EU-TIRADS 5 thyroid nodules. Issue 5 (May 2021) - Rozenbaum, A; Buffet, C; Bigorgne, C; Royer, B; Rouxel, A; Bienvenu, M; Chereau, N; Menegaux, F; Leenhardt, L; Russ, G
Abstract : Objective: Active surveillance of cytologically proven microcarcinomas has been shown as a safe procedure. However, fine needle aspiration biopsy (FNAB) is not recommended by European Thyroid Association (ETA) and American Thyroid Association (ATA) guidelines for highly suspicious nodules ≤ 10 mm. The aim of the study was to assess the outcomes of active surveillance of EU-TIRADS 5 nodules ≤ 10 mm not initially submitted to FNAB. Patients and methods: 80 patients with at least one EU-TIRADS 5 nodule ≤ 10 mm and no suspicious lymph nodes, accepting active surveillance, were included. Results: Mean baseline diameter and volume were 5.4 mm (±2.0) and 64.4 mm 3 (±33.5), respectively. After a median follow-up of 36.1 months, a volumetric increase ≥ 50% occurred in 28 patients (35.0%) and a suspicious lymph node in 3 patients (3.8%). Twenty-four patients underwent an FNAB (30.0%) after at least a 1 year follow-up of which 45.8% were malignant, 8.3% benign, 33.3% undetermined and 8.3% nondiagnostic. Sixteen patients (20.0%) underwent conversion surgery after a median follow-up of 57.2 months, confirming the diagnosis of papillary carcinoma in 15/16 cases (not described in 1 histology report), all in remission at 6–12 months postoperative follow-up. Conclusion: Applying ETA and ATA guidelines to avoid FNA of EU-TIRADS 5 sub-centimeter nodules and proceeding to active surveillance of such nodules in selected patients is a safe procedure. Thus, US-FNAB could be postponed until the nodule shows signs of progression or a suspicious lymph node appears, with no added risk for the patient.